Consumer Choices Regarding the Application of Integrated Marketing Communication (IMC) Strategies at Yoong Motor Indonesia - Kevin UTOMO; Hilda Yunita WONO (PT Keberlanjutan Strategis Indonesia, 2025)
Social media has become a fundamental aspect of daily life, including in Indonesia, where numerous businesses, including those in the automotive industry, utilize it to drive sales and enhance their market reach. Through platforms like Instagram and YouTube, Yoong Motor Indonesia has effectively showcased its products, engaged with customers, and expanded its branch network across the country. The goal of this study is to understand consumer preferences regarding the Integrated Marketing Communication (IMC) approach used by Yoong Motor Indonesia, a company specializing in the sale of vehicle lighting. This research uses a quantitative descriptive method, which outlines issues based on data without comparing variables. The sample consisted of 100 consumers of Yoong Motor Indonesia, selected through purposive sampling, and a Likert scale-based questionnaire was used for data collection. The validity of the instrument was tested with an r value greater than 0.3, while reliability was assessed using Cronbach’s Alpha, which exceeded 0.6. The data was analyzed using weighting and average calculations to assess consumer preferences. The findings show that Yoong Motor Indonesia’s IMC strategy successfully impacted consumer preferences through integrated communication channels like social media, direct marketing, sales promotions, and sponsorships. The study confirmed that the questionnaire was both valid and reliable, with a significance value of less than 0.05 and a Cronbach’s Alpha higher than 0.7. The most influential IMC strategy was digital marketing (1.89), followed by advertising (1.95), sponsorship (1.96), sales promotions (2.10), and direct marketing (2.24).